The Influence of Digital Marketing, Selling Price, Personal Selling, Brand Image, and Distribution Channels on Sales Volume of SR12 Herbal Skincare Products in Wonosobo - M. Trihudiyatmanto; Bahtiar Efendi; Putri Alifia Nur Laily (Business, Accounting, and Knowledge Journal, 2025)
This study aims to analyze the influence of digital marketing, selling price, personal selling, brand image, and distribution channels on the sales volume of the SR12 herbal skincare product consumers in Wonosobo City, Central Java, Indonesia. The research method used in this study is quantitative. The population in this study consisted of 130 consumers of SR12 herbal skincare products in Wonosobo City. Based on the Slovin formula, the sample used in this study was 99 respondents. The sampling technique used in this study was probability sampling with the simple random sampling type. The data analysis technique in this study was multiple linear regression analysis. The results of this study indicate that the variables of digital marketing, selling price, personal selling, brand image, and distribution channels have a positive effect on sales volume. This finding indicates the importance of digital marketing, selling price, personal selling, brand image, and distribution channels in increasing the sales volume of a product, especially SR12 Herbal Skincare products in Wonosobo City.